THE EFFECT OF TAX PLANNING AND TAX BURDEN ON EQUITY IN BANKING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2021-2023 - Ahmad Junaidi; Ummul Khair; Dinal Eka Pertiwi; Tiara Nopita Lestari (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Taxes are mandatory contributions from citizens to the state that are enforced by law and used to finance state expenditures for the public interest and welfare of society. Taxes are a major source of state revenue that is important for national development. This study aims to analyze the impact of tax planning and tax burden on equity in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The research method used is quantitative with secondary data obtained from various published sources. A sample of 29 companies was selected from a population of 47 using purposive sampling, and analyzed using SPSS version 26. The results show that tax planning does not have a significant effect on equity, as seen from the p-value of 0.691 and the path coefficient value of -0.399, which is negative. Tax burden has a positive and significant effect on motorized equity, as seen from the p-value of 0.005 and the path coefficient value of 2.927, which is positive. Tax planning and tax burden have a positive and significant combined effect on equity, as indicated by a p-value of 0.015 and a path coefficient of 4.437, which is positive